Linking Land Surface Temperature and Tourist Thermal Comfort: Implications for Sustainable Tourism Development in Bali, Indonesia - Rois Dinan; MH Nateq Nouri; Fardiah Qonita Ummi Naila (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2025)
Tourism is widely recognized as one of the most climate-sensitive economic sectors, with destinations in tropical regions increasingly exposed to the impacts of global warming and rapid urbanization. Rising temperatures and the intensification of urban heat island effects have become critical challenges for tourist thermal comfort, destination competitiveness, and the sustainability of tourism development worldwide. As a globally renowned tourism destination, Bali faces growing environmental pressures associated with land-use change and expanding built-up areas; however, empirical studies linking surface temperature dynamics with tourism comfort remain limited. This study aims to analyze the spatiotemporal dynamics of Land Surface Temperature (LST) in Bali Province and assess their implications for tourist thermal comfort and sustainable tourism planning. A remote sensing-based analysis was conducted using satellite imagery from 2014 and 2024 to identify LST changes and evaluate thermal conditions in major tourism hotspots. Thermal comfort benchmarks were established based on internationally recognized thermal comfort indices and tourism climate literature to determine whether current temperature conditions remain within acceptable comfort thresholds. Land cover change analysis was also performed to examine the relationship between land-use transformation and surface temperature variations. The results indicate a significant increase in LST across key tourism areas, particularly in densely urbanized environments, with several popular destinations exceeding optimal thermal comfort ranges. These findings suggest potential risks to visitor experience and long-term destination attractiveness. The study emphasizes the importance of integrating LST and thermal comfort considerations into tourism and spatial planning and provides a replicable methodological framework.